2021
DOI: 10.1155/2021/6668095
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Temperature on Multitrays in an Indirect Solar Dryer (ISD) with Energy Storage and Three Airflow Modes

Abstract: This work presents the regulation of temperature in an indirect multitrays solar dryer with oriented flux under the irradiance fluctuation. The temperature regulator using a negative temperature coefficient (NTC) as a sensor and fans is designed, and a similar device is also used to measure humidity through a sensor. Inlet and outlet dryer temperature and temperature on the three trays have been recorded with the regulation system according to different airflow modes. Irradiance and humidity have also been rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The climate inside the dryers is more controllable with an average temperature of 30-60 • C [28], which almost doubles the temperature measured in the outside atmosphere. One study found that temperatures can be maintained at 50-52 • C in different trays [29] and some mentioned that during the peak hour the temperature can reach 62 • C, which is almost twice the ambient temperature [30], which can heat up the air inside faster and lead to faster fish drying. In short, there are many advantages that can be obtained from using solar dryers when compared to other drying processes, such as shortening the drying period, producing better quality of dried fish and reducing energy consumption [31].…”
Section: Of 25mentioning
confidence: 99%
“…The climate inside the dryers is more controllable with an average temperature of 30-60 • C [28], which almost doubles the temperature measured in the outside atmosphere. One study found that temperatures can be maintained at 50-52 • C in different trays [29] and some mentioned that during the peak hour the temperature can reach 62 • C, which is almost twice the ambient temperature [30], which can heat up the air inside faster and lead to faster fish drying. In short, there are many advantages that can be obtained from using solar dryers when compared to other drying processes, such as shortening the drying period, producing better quality of dried fish and reducing energy consumption [31].…”
Section: Of 25mentioning
confidence: 99%